The Influence of Risk Perception, Trust, Ease of Use, and Benefits on the Decision to Use QRIS in Agricultural Commodity Purchases - Priambudi Firman Fajari; Juwarin Pancawati; Aris Supriyo Wibowo (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
The rapid expansion of digital payment systems in Indonesia has positioned QRIS (Quick Response Code Indonesian Standard) as a strategic instrument to accelerate financial inclusion, particularly in traditional markets. However, consumer adoption remains uneven, requiring deeper investigation into the behavioral factors that shape household decision-making. This study aims to examine the influence of perceived risk, trust, perceived ease of use, and perceived benefits on household consumers’ decisions to adopt QRIS in the context of traditional market transactions. Data were collected from household consumers at Pasar Anyar, Tangerang, using a structured questionnaire. The responses were analyzed with SPSS to test the significance of the proposed variables in influencing QRIS adoption decisions. The findings reveal that trust and perceived benefits significantly affect consumers’ decisions to use QRIS, while perceived risk and ease of use show no meaningful impact. Among the variables, perceived benefits emerge as the most dominant factor, as consumers value transaction speed and improved expenditure management. Trust also plays a critical role, reflecting the necessity of security assurance before shifting from cash-based payments. The study highlights that strengthening consumer trust and emphasizing tangible benefits are essential to enhance QRIS adoption in traditional markets. Policy recommendations include targeted consumer education, merchant incentives, and sustainable payment infrastructure to ensure smooth and secure digital transactions.